The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s11205-016-1526-8
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Infant Mortality in Older ASEAN Economies

Abstract: Infant mortality in the Association of Southeast Asian Nations (ASEAN) has been declining, yet disparities remain between the nations. This paper therefore explores the determinants of infant mortality in the older ASEAN economies, Malaysia, Thailand, Indonesia and the Philippines. The key findings of the study are: First, there is evidence of long-run relationships among infant mortality, education, female fertility, income and access to healthcare. Second, the determinants of infant mortality vary between co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 49 publications
2
11
0
Order By: Relevance
“…used panel cointegration technics in a sample of 21 Organization for Economic Cooperation and Development (OECD) countries over the period1975-2001, to explain the relationship between health care and expenditure and GDP. The negative relationship between per capita real GDP and infant mortality rate is also consonant with other studies such asSubramaniam et al (2018) Silva (2007). applied a panel stationarity test to the infant mortality rate in Australia from 1911 to 2002, which allows for disruptions in both the level and trend of the series.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…used panel cointegration technics in a sample of 21 Organization for Economic Cooperation and Development (OECD) countries over the period1975-2001, to explain the relationship between health care and expenditure and GDP. The negative relationship between per capita real GDP and infant mortality rate is also consonant with other studies such asSubramaniam et al (2018) Silva (2007). applied a panel stationarity test to the infant mortality rate in Australia from 1911 to 2002, which allows for disruptions in both the level and trend of the series.…”
supporting
confidence: 91%
“…For instance , Bishai, (1995), Dreger and Reimers (2005). Silva (2007), Erdoğan et al (2013), Gil-Alana et al (2017, Subramaniam et al (2018) and Yaya et al (2019) have all focused on the persistence of infant mortality in developed countries or Asian countries. Income poverty and health poverty might not necessarily follow the same directions and the determinants of the two components of poverty might not necessarily be the same (Musakwa and Odhiambo 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, we found that a 10 per cent increase in per capita real GDP, on average, reduced infant mortality rates by approximately 0.2 per cent. This negative relationship between per capita real GDP and infant mortality rate is also consonant with that of previous studies (e.g., Gbesemete & Jonsson, 1993;Subramaniam et al, 2018;Zakir & Wunnava, 1999).…”
Section: Resultssupporting
confidence: 92%
“…This study will contribute to existing literature by looking at infant mortality from a broader perspective by using a global data set. In addition, it also proposes to introduce new explanatory variables in the form of technology and governance factors into its proposed model as the impact of these factors on infant mortality have not been critically evaluated in previous studies (Frey & Field, 2000;Mukherjee & Kizhakethalackal, 2013;Subramaniam, Loganathan, Yerushalmi, Devadason, & Majid, 2018;Wellington, 2014;Zakir & Wunnava, 1999) which have generally focused on the roles of gross domestic product (GDP), female education, female fertility and health quality in determining infant mortality rates. Good governance constituents such as political stability, effective governance, low corruption and elevated personal and property rights provide a secure environment that encourages stakeholders to invest in medical products and health-related infrastructure that eventually improve the overall quality of health services, thus contributing to reductions in infant mortality rates.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Figure 1b illustrates the maternal mortality rate in Indonesia, which experienced a decrease until 2007 but showed a leap in 2010. Apart from the constant decline from year to year, Indonesia is still ranked second in Southeast Asia after Laos for infant mortality rate (Subramaniam et. al., 2016).…”
Section: Introductionmentioning
confidence: 99%